Travel Motivation and Domestic Tourist Satisfaction in Bali, Indonesia - Filda Rahmiati; Norfaridatul Akmaliah Othman; Vincent Bonavisi (Sekolah Tinggi Manajemen IPMI, 2018)
Bali has been selected as the best tourist destination in Indonesia, which have been popular worldwide. This research aimed to analyze the domestic tourist satisfaction in Bali based on Motivation factors. Previous studies supported that motivation could encourage and attract someone to do tourism activities and expecting satisfaction. This research used a quantitative research method to evaluate the motivation factors of Relaxation, Prestige, Cultural, and Accessibility on Tourist Satisfaction. Non-probability sampling with convenience sampling was used in this study. Questionnaires was distributed to 110 tourist tested with validity and reliability before data analysis. All the indicators are valid and reliable which further analyze motivation factors on tourist destination. Data analysis used in this research were multiple linear regression. The result afirmed that relaxation, cultural, and accessibility have significant on tourist satisfaction in Bali, hence, prestige has no significant on tourist satisfaction. Further, all motivation factors have simultaneously significant on tourist satisfaction in Bali with 76.3% of adjusted R2.